Religion and Revolution: Spiritual and Political Islam in Ernesto Cardenal By John Andrew Morrow (Newcastle Upon Tyne, UK: Cambridge Scholars Publishing, 2012. hbk. 339 pages.) (American Journal of Islam and Society, 2013)
In his Religion and Revolution: Spiritual and Political Islam in Ernesto Cardenal,John Morrow has manifested his years-of-research incorporated knowledgein Hispanic, Native American, and Arabic-Islamic studies to shed lighton two poorly understood themes – both in the East and, particularly, in theWest – via a specific narrative. The themes are, broadly speaking, those ofSufism and the Islamic Republic of Iran. The narrative is the story of ReverendFather Ernesto Cardenal, a Nicaraguan revolutionary Christian priest who hadprogressively acquired some spiritual and revolutionary interests in Islam aftervisiting certain Middle Eastern countries, especially Iran.Whether Cardenal is seen as merely a medium for Morrow to expresshis own findings on Sufism and Iran or as an end in itself is up to the reader.Either way, Morrows’ on-the-whole impartial and unbiased interpretation ofIslam, Sufism, and Iran, indirectly through the personality and writings ofCardenal, constitutes a calibre of work rarely seen or read in the westernmedia and literature. This is mostly due to its seemingly close, albeit academic,sympathy with elements of Iran’s right “conservative” and “hardline”elite. Perhaps that is why, at times, one feels that the author has stepped uphis defence a shadow too much. The manner he has raised and evaluatedsome of the data he presents, as well as some of the rumours – against Sufismand especially Iran – he refutes, clearly demonstrates that he has exploredand gained access to (1) the pristine image of Sufism and notable Sufis and ...